Disruption of the Interfacial Membrane Leads to Magnaporthe oryzae Effector Re-location and Lifestyle Switch During Rice Blast Disease - Jones, Kiersun; Zhu, Jie; Jenkinson, Cory B.; Kim, Dong Won; Pfeifer, Mariel A.; Khang, Chang Hyun (Frontiers in Cell and Developmental Biology, 2021)
To cause the devastating rice blast disease, the hemibiotrophic fungus Magnaporthe oryzae produces invasive hyphae that are enclosed in a plant-derived interfacial membrane, known as the extra-invasive hyphal membrane (EIHM), in living rice cells. Little is known about when the EIHM is disrupted and how the disruption contributes to blast disease. Here we show that the disruption of the EIHM correlates with the hyphal growth stage in first-invaded susceptible rice cells. Our approach utilized GFP that was secreted from invasive hyphae as an EIHM integrity reporter. Secreted GFP (sec-GFP) accumulated in the EIHM compartment but appeared in the host cytoplasm when the integrity of the EIHM was compromised. Live-cell imaging coupled with sec-GFP and various fluorescent reporters revealed that the loss of EIHM integrity led to shrinkage and eventual rupture of the rice vacuole. The vacuole rupture coincided with host cell death, which was limited to the invaded cell with presumed closure of plasmodesmata. We report that EIHM disruption and host cell death are landmarks that delineate three distinct infection phases (early biotrophic, late biotrophic, and transient necrotrophic phases) within the first-invaded cell before reestablishment of biotrophy in second-invaded cells. M. oryzae effectors exhibited infection phase-specific localizations, including entry of the apoplastic effector Bas4 into the host cytoplasm through the disrupted EIHM during the late biotrophic phase. Understanding how infection phase-specific cellular dynamics are regulated and linked to host susceptibility will offer potential targets that can be exploited to control blast disease.